Ca(2+) signaling behaviours of intramuscular interstitial cells of Cajal in the murine colon - Drumm, Bernard T. (J Physiol, 2019)
A component of the SIP syncytium that regulates smooth muscle excitability in the colon is the intramuscular class of interstitial cells of Cajal (ICC-IM). All classes of ICC (including ICC-IM) express Ca(2+) activated Cl(−) channels, encoded by Ano1, and rely upon this conductance for physiological functions. Thus, Ca(2+) handling in ICC is fundamental to colonic motility. We examined Ca(2+) handling mechanisms in ICC-IM of murine proximal colon expressing GCaMP6f in ICC. Several Ca(2+) firing sites were detected in each cell. While individual sites displayed rhythmic Ca(2+) events, the overall pattern of Ca(2+) transients was stochastic. No correlation was found between discrete Ca(2+) firing sites in the same cell or in adjacent cells. Ca(2+) transients in some cells initiated Ca(2+) waves that spread along the cell at ~100μm per sec. Ca(2+) transients were caused by release from intracellular stores, but depended strongly on store-operated Ca(2+) entry mechanisms. ICC Ca(2+) transient firing regulated the resting membrane potential of colonic tissues as a specific Ano1 antagonist hyperpolarized colonic muscles by ~10 mV. Ca(2+) transient firing was independent of membrane potential and not affected by blockade of L- or T-type Ca(2+) channels. Mechanisms regulating Ca(2+) transients in the proximal colon displayed both similarities and differences with the intramuscular type of ICC in the small intestine. Similarities and differences in Ca(2+) release patterns might determine how ICC respond to neurotransmission in these 2 regions of the GI tract.